PENGARUH MEDIA PEMBELAJARAN KOTAK SURAT PERKALIAN MATEMATIKA TERHADAP PEMAHAMAN DAN MOTIVASI BELAJAR SISWA DI SDN TENGKET 1 - Haliza, Nur; Arifin, Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine whether there is an influence of the mathematics multiplication mailbox learning media on students' understanding and motivation to learn in mathematics subjects, multiplication concept material in class III students at SDN Tengket 1. This research uses a quantitative approach with a Pre-Experimental Designs research design with the type One Group Pretest-Posttest. The instruments in this research consisted of test instruments (questions) and non-test instruments (questionnaires). The population and sample were 30 class III students at SDN Tengket 1. The data analysis techniques used are validity test, reliability test, normality test, and paired sample t-test. Researchers used the SPSS V21.0 software application. The results of the research show that there is an influence of the mathematics multiplication mailbox learning media on the understanding and learning motivation of class III students at SDN Tengket 1 as shown by the results of the sig value. (2-tailed) is 0.000 < 0.05, which means there is a difference in the average score in students' understanding and motivation to learn, namely the average score for understanding on the pretest is 60.33 and posttest is 78.67, while the average score for learning motivation on the pretest is 66.93 and posttest was 77.67.